Dataset for additional information on the evaluation of thermal properties of thin films by IR radiometry using a comprehensive set of Zr-O-N thin films - Silva-Oliveira, C. I. (2020)
This paper provides additional negative data regarding the paper Evaluation of thermal properties of thin films by IR radiometry using a comprehensive set of Zr-O-N thin films. In that paper, a matrix of samples was prepared to evaluate the so-called Extremum method for the analysis of Infrared (IR) radiometry data. Such matrix was composed by 3 types of films with 4 different thickness in 3 types of substrates, totalizing 36 samples in total. The data of this paper can be divided into three separate categories: i) lack of adhesion of the films deposited on Teflon, simultaneously to the films deposited on other substrates. ii) Improvement of the signal and signal-to-noise ratio on samples that did not present an extremum (minimum or maximum) using the initial (more conventional) way of measurement. iii) It is also presented a failed fitting of the IR radiometry data created with entangled material parameters. All this data is relevant for researchers devoted to measurement of thermal properties of thin films by IR radiometry that employ the two layer model and Extremum Method.